2018
DOI: 10.1016/j.worlddev.2018.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Maternity protection in formal and informal economy workplaces: The case of Ghana

Abstract: Full bibliographic details must be given when referring to, or quoting from full items including the author's name, the title of the work, publication details where relevant (place, publisher, date), pagination, and for theses or dissertations the awarding institution, the degree type awarded, and the date of the award.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…Our study has important implications for the design of MLPs in developing countries like Pakistan. Our study reaffirms the finding (Stumbitz, Lewis, Kyei, et al, 2018) that it is important to account for heterogeneities in women workers, for example, based on the type (public/private) and size (small, medium, large) of employing organization, and employment type (contract-based, entrepreneurial or formal). Our data suggests that women working as regular employees in public hospitals generally have better overall access to maternity policies.…”
Section: Implications For Policy and Research On Mlpssupporting
confidence: 88%
“…Our study has important implications for the design of MLPs in developing countries like Pakistan. Our study reaffirms the finding (Stumbitz, Lewis, Kyei, et al, 2018) that it is important to account for heterogeneities in women workers, for example, based on the type (public/private) and size (small, medium, large) of employing organization, and employment type (contract-based, entrepreneurial or formal). Our data suggests that women working as regular employees in public hospitals generally have better overall access to maternity policies.…”
Section: Implications For Policy and Research On Mlpssupporting
confidence: 88%
“…With a few exceptions (e.g., Gatrell, 2019), research on maternal body work has also mostly focused on women in highly skilled, professional occupations (Stumbitz, Lewis, Kyei, et al, 2018). Gatrell (2019) argued that continued breastfeeding beyond a few weeks of a baby's birth was problematic especially for low-income mothers needing to combine paid work and breastfeeding.…”
Section: Northern Knowledge Hegemony and The Importance Of Context:mentioning
confidence: 99%
“…Like work on the broader concept of 'body work' (Coffey, 2016), the literature on maternal body work and organizations has primarily been developed in the global North (Stumbitz, Lewis, Kyei, & Lyon, 2018), neglecting views on bodies and the specific nature of families, employment and societies in the global South. For example, in South Africa, colonial and apartheid legacies of unequal education, land distribution by race and migrant labour influence the nature of family forms, working conditions and employment.…”
Section: Northern Knowledge Hegemony and The Importance Of Context:mentioning
confidence: 99%
“…In this wide range of views, it can be seen easily that participants who had shown positive attitude towards pregnancy and maternity at workplace, at some point expressed their concern regarding difficulties, which small organizations have to face in handling this situation. Small organizations, no doubt, see pregnancy at workplace as a potential problem that they have to handle, not a welcoming situation [7] . For small organizations, the hostility factors against pregnancy and maternity at work place come from the fact that they, generally, don't support labour law and has resentful attitude towards maternity act specially.…”
Section: Employer's Perceptions Regarding Pregnancy At Workplacementioning
confidence: 99%
“…In many instances, employers reported that their employee had said that they would join but did showed up after leaves Female employers were sympathetic about this but male employers were clearly not ready to accept the situation. This issue was noted more upsetting for small employers [6,7] . "Mostly the female workers don't return to their jobs after delivery and we have to hire another person for that job.…”
Section: Re-joining the Jobmentioning
confidence: 99%